Accountability do cumprimento das decisões da Corte IDH: estudo dos casos dos países do Mercosul em fase de execução de sentença - Anelli, Thaís Bordin (2018)
This dissertation is a theoretical and practical reflection on the duty of states to fulfill their obligations under international treaties. In the 21st century, there was an intensification of jurisdictional dialogues. The internationalization of law, through the movement of actors, norms and factors, shows that global governance as a responsible conduct of state affairs is multicentric and decision making is transformed by characteristics such as transparency and greater participation of stakeholders in decision making. Responsibility explains the need for states to be accountable for their actions. The space-time delimitation of the investigation refers to the Inter-American System for the Protection of Human Rights, in particular by the Inter-American Court in relation to the cases of the Mercosur countries, during the supervision phase of the sentence. The research problem is: to what extent is the responsibility of the Mercosur countries for the convictions of the Inter-American Court of Human Rights? In order to find answers to this question, the deductive approach method is used to present two arguments, the greater the duty of States to comply with the decisions of the Inter-American Court and the smaller is the study of the cases of Mercosur countries in the fulfillment of the judgments, in order to reach a conclusion as to whether States are responsible. The procedure method is the one of bibliographical research and documentary analysis, with the help of the technique of search of abstracts and synthesis of data. The first chapter addresses the phenomena of jurisdictional dialogues, the internationalization of law, global governance, and accountability issues. The relationship between national and international law, the rules of the Inter-American Court, and the provisions relating to the internalization of international treaties in Argentine, Brazilian, Paraguayan and Uruguayan national law are verified. The specific objective of this part of the work is to delineate the theoretical delimitations that base the evaluation of the cases of the next phase. The second chapter consists of three interpretive axes. The first axis makes the numerical mapping of the cases, the second identifies the details of the cases and the third one checks the conformity status of the decisions. The specific objective of this chapter is to analyze the responsibility of the Mercosur States for the reparation measures established by the Inter-American Court of Human Rights. The investigation has identified that States comply, in parts, with the determinations of the regional court, with conformity varying according to the category of reparation measure. The progress of State responsibility is remarkable, but action is still needed to increase the effectiveness of human rights protection.